PEMBERDAYAAN POTENSI DESA DAN PENERAPAN TEKNOLOGI PENGERING PADA INDUSTRI TENUN PEWARNA ALAMI DAN KERAJINAN ATE DI DESA SERAYA TIMUR KARANGASEM – BALI - Sugita, I K. G.; Priambadi, I G N; Suarnadwipa, N (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi)
The East Seraya village is a village that has some potential to be developed. The economic potential of the village comes from the marine products and the creative industries of weaving and craftsmen of ate. The natural beauty of the village while the potential to be developed as a tourist attraction/ tour support, which is supported by the position of Seraya village located at the tip and the tourist track Amed travel. Weaving craftsmen gathered in a group that named is " KARYA SARI WARNA ALAMI ". The motive of weaving and coloring system has distinctive features. Coloring materials derived from the leaves and plants that live in the village of Seraya. The potential development of handicrafts and weaving ate very potential to be developed, because the Seraya Village is a tourist track between Ujung and Amed vilages. KKN PPM programme is developing programs to empower creative industries and training program based on rural potentia, Applications dryers systems production quality. The purpose of aplication dryer machine system in weaving craft group and ate is to improve the quality of production. Educational and vocational training aimed to youth groups, farm groups, fishing groups. Community socials empowerment programs to enhance the creative economy is going to go well if it gets assistance by the college. College as a facilitator in the implementation of education and training, and memotivor community in order to improve people's lives.
Keywords: Seraya village, weaving, ate, drying machine